A predictive modeling tool for damage analysis and design of hydrogen storage composite pressure vessels. (17th June 2021) - Nguyen, Ba Nghiep; Roh, Hee Seok; Merkel, Daniel R.; Simmons, Kevin L.
Abstract: In this paper, a predictive modeling tool is developed for damage analysis and design of hydrogen (H2 ) storage composite pressure vessels. It integrates micromechanics of matrix cracking into a continuum damage mechanics (CDM) description for damage evolution, and three-dimensional (3D) finite element (FE) modeling of the vessel structural response. At the scale of the composite layer (mesoscale), the temperature-dependent stiffness reduction law in terms of the damage variable for transverse matrix cracking is computed using an Eshelby-Mori-Tanaka approach (EMTA) for the initial composite thermoelastic properties and a self-consistent model for the stiffness reduction as a function of the damage variable. While transverse matrix cracking obeying a damage evolution relation can progressively evolve from an initiation to a saturation state, fiber failure is predicted by a micromechanical fiber rupture criterion that accounts for the fiber strength and matrix stress that can be computed within EMTA. The implementation of this integrated multiscale modeling model into a 3D FE formulation enables damage analysis and design of H2 storage composite pressure vessels. The developed tool is illustrated through 3D damage analyses of a cryogenically compressed H2 storage vessel model subjected to thermomechanical loadings to investigate effects of the helical layer fiber orientation and loading scenario on damage development, vessel integrity and burst pressure. Highlights: A predictive modeling tool for damage analysis and design of hydrogen storage vessels was developed. The tool integrates matrix cracking micromechanics into a continuum damage mechanics formulation. Fiber failure is predicted by a micromechanical criterion. Finite element damage analyses of a hydrogen storage vessel were performed under two loading scenarios. The effects of loading scenario and helical layer's orientation on vessel integrity were studied.